Evaluating the behaviour of Chinese stakeholders engaged in large hydropower projects in Asia and Africa - Tan-Mullins, May; Urban, Frauke; Mang, Grace (Cambridge University Press, 2017)
Hydropower dams have been back in the spotlight due to shifting preference for low carbon energy generation and possible contributions to mitigating climate change. At the forefront of the renaissance of large hydropower dams are Chinese companies as the world’s largest dam builders at home and abroad, opening up opportunities for low and middle income countries. However, large hydropower dams, despite their possible developmental and carbon reduction contributions, are accompanied by huge economic costs, profound negative environmental changes and social impacts. Using fieldwork data from four hydropower projects in Ghana, Nigeria, Cambodia and Malaysia, this paper evaluates the behavior of Chinese stakeholders engaged in large hydropower projects in Asia and Africa. We do this by first exploring the interests of the different Chinese stakeholders and then investigating the wider implications of these Chinese dams on the local, national and international contexts. The paper concludes that hydropower dams will continue to be prominent in the future to increase energy security and reduce energy poverty world-wide hence the planning, building and mitigation strategies need to be done in a more sustainable way that takes into account national development priorities, the needs of local people and the impacts on natural habitats.